Human interleukin-4-dependent facilitation of human IgG production in PBL-NOG-hIL-4-Tg mice - Kametani, Yoshie; Ohshima, Shino; Ito, Ryoji; Ohno, Yusuke; Yamada, Soga; Hoshino, Yuki; Miyamoto, Asuka; Suzuki-Ohno, Mao; Katano, Nagi; Tsuda, Banri; Miyazawa, Mariko; Kashiwagi, Hirofumi; et al. (Frontiers in Immunology, 2025)
Immune-humanized mouse models are indispensable tools for evaluating human immune responses and testing immune-based therapies; however, the induction of robust human antigen-specific immunoglobulin G (IgG) production remains limited due to species-specific incompatibilities. To investigate how human interleukin-4 (IL-4) promotes antibody responses, we employed NOG-hIL-4 transgenic mice (NOG-hIL-4-Tg), which constitutively express human IL-4, and transplanted them with human peripheral blood mononuclear cells (PBMCs). Flow cytometry, histological analysis, and next-generation sequencing were used to assess human lymphocyte maintenance, receptor repertoire diversity, class switching, and antigen-specific responses following immunization with peptide antigens. Sustained human B cell maintenance correlated with defined supraphysiological ranges of plasma hIL-4 concentrations. T and B cell receptor repertoire analyses demonstrated stable clonal diversity for one month after engraftment, followed by contraction by three months. Immunoglobulin repertoire profiling revealed IL-4–dependent class switching to IgG, with early predominance of IgG3 that declined over time and a gradual increase in IgG1, though subclass distribution varied among donors. Immunization induced antigen-reactive IgG, although many clones displayed low-affinity or cross-reactive binding, consistent with limited affinity maturation. Histological examination revealed tertiary lymphoid structure–like accumulations of human B and T cells within the spleen, without fully developed germinal centers. These findings demonstrate that human IL-4 expression in NOG-hIL-4-Tg mice supports human B cell survival, class switching, and partial IgG maturation, providing a relevant platform for studying human humoral immunity and evaluating antibody-based immunotherapies.